Bodies in Transit: Re-thinking vulnerability and resistance in post-colonial neo-Victorian literature and culture - Romero-Ruiz, María Isabel (My University, 2019)
The aim of my participation in this round table is to make an approach to an analysis of contemporary historical fiction through the lens of theories of vulnerability and resistance. In particular, I would like to address postcolonial neo-Victorian fiction in the light of Judith Butler’s most recent ideas. One of the main features of neo-Victorianism is the re-writing of the Victorian past to discuss contentious topics of the present. The presence of Victorian culture in our contemporary societies is so outstanding that issues that preoccupied the Victorian mind such as violence, sexuality or Empire have become the main topics of controversy in neo-Victorian productions of our time. On this particular occasion, I am very interested in making an analysis of how the Victorian colonial setting has an echo in new forms of imperialism. The relations between the metropolis and its colonised territories around the world in the nineteenth century can be seen as the forerunners of the relationships between old colonial powers like England and its old colonised subjetcs in Africa, Asia or Australia today. In this way, “traces” of the colonial past can be discerned in our postcolonial globalised ways of governing the planet. In this sense, the notion of the “Neo-Victorians-at-sea”, coined by Elizabeth Ho, becomes essential in the urdenstanding of England’s colonial and post-colonial power and its consequences for the re-writing of a history where the voices of “the other” can be heard. This notion of the voyage where identities become fluid with the sea and dependent on one another is especially relevant; even the ship can be envisioned as the colonial scenario where postcolonial encounters take place. Re-writing history means resorting to nostalgia as a tool to remember the past, but at the same time post-colonialism can be interpreted as a memorial practice.
Keywords: Colonialismo; Bodies; Vulnerability; Resistance; Post-colonial; Neo-Victorian